PENERAPAN TEKNIK PARTISIPATORY RAPID APPRAISSAL (PRA) DALAM PENGELOLAAN LINGKUNGAN DI DATARAN TINGGI NUSA TENGGARA TIMUR - Made Merta (Environmental Research Center (PPLH) of Udayana University)
Research on slash and burning practices was conducted in Kecamatan Insana,TimorTengah Utara Regency on August , 2004. The research aim is for better understanding ,why the community practicing this method and tray to stop it. This research usedPRA technique ,because PRA is a participatory approach , new innovation method forimproving efficacy and rapidity in data collection. Research concluded that thecommunity become conscious there was serious declines in ecosystem due to slash andburning practice. The farmers need counseling, extension and demonstration on usinghoe, sickles etc. Participatory method was interested the community in prepare theaction program and developing the learning process for solving the environmentproblems.